Acute and repeated intranasal oxytocin administration exerts anti-aggressive and pro-affiliative effects in male rats. (January 2015) - Calcagnoli, Federica; Kreutzmann, Judith C.; de Boer, Sietse F.; Althaus, Monika; Koolhaas, Jaap M.
Highlights: Intranasal OXT reduces offensive aggression in male resident rats. Intranasal OXT increases social exploration toward an unfamiliar male intruder. Intranasal OXT strengthens bonding between a male rat and its female partner. Summary: Socio-emotional deficits and impulsive/aggressive outbursts are prevalent symptoms of many neuropsychiatric disorders, and intranasal administration of oxytocin (OXT) is emerging as a putative novel therapeutic approach to curb these problems. Recently, we demonstrated potent anti-aggressive and pro-social effects of intracerebroventricular (icv) OXT administration in male rats. The present study tested whether similar behavioral effects are induced when OXT is delivered intranasally. Heart-rate and blood-pressure responses were telemetrically monitored to investigate whether peripheral physiological effects were provoked after intranasal OXT administration. Intranasal OXT administration in resident animals reduced offensive aggression and increased social exploration toward an unfamiliar male intruder. Using a partner-preference test, intranasal OXT also strengthened the bonding between the male resident and its female partner. No changes in cardiovascular (re)activity were found, indicating an absence of direct peripheral physiological effects after intranasal OXT treatment. In conclusion, although the precise route and mechanisms of nose-to-brain transport/communication remain to be elucidated, our data demonstrated intranasal OXT to be an effective application method for suppressing intermale aggression and enhancing social affiliation.